Legal and ethical challenges in cybersecurity governance: a South African perspective on corporate responsibility and protection against cybercrimes - Morape, Emerentia Morape (Department of Commercial Law, 2026)
In the current digital era, cybersecurity has become a vital aspect of corporate governance, presenting challenging moral and legal issues for businesses all over the world. This dissertation examines the complex relationship between legal frameworks, ethical deliberations, and organisational duties as they relate to cybersecurity within the context of corporate governance. It clarifies the dynamic nature of cybersecurity rules and regulations by looking at different case law and journal papers, highlighting the necessity of taking preventative action to reduce cyber risks and guarantee compliance. This paper also explores the many cybercrimes as defined by the Cybercrimes Act 19 of 2020, the various laws governing cybersecurity in South Africa, as well as the ethical aspects of cybersecurity, and how privacy and data protection are addressed. It highlights how crucial it is for businesses to have a culture of ethical consciousness and responsibility in order to protect sensitive data and maintain stakeholder trust. This dissertation offers insightful guidance and useful suggestions for managing the complicated realm of cybersecurity in corporate governance, strengthening organisational resilience and integrity against constantly changing cyberthreats, by means of an extensive examination of legal and ethical implications.